Evaluation of Irrigation System Performance In Ujungjaya Irrigation Area Sumedang Regency - Siswanto, Donny; Sulistijo, Sulistijo; Nurdiyanto, Nurdiyanto (Ann Publisher, 2024)
Water is a human life that must be managed and maintained for sustainability. Water for agricultural businesses can be fulfilled through rainwater or an irrigation system, starting from the dam flowing through the network or irrigation canal from the main canal to the tertiary plots of rice fields. For this reason, it is necessary to evaluate the performance of the existing irrigation system. According to the Regulation of the Minister of PUPR RI No.12/PRT/M/2015, it can be stated that the Performance Condition of the Ujungjaya Irrigation System in Sumedang Regency currently has a performance with a value of 43.41% with Poor Performance Criteria (< Value of 55%), while the Real Needs for Operation and Maintenance (AKNOP) of the Ujungjaya Irrigation Area per year is Rp.3,073,990,000,- or Rp. 1,917,648,,- rounded up to Rp.1,900,000,- per hectare (Ha). With the division for Operational Administration activities, OP activities are Rp. 709,300,,- or around 23.07%, the rest, which is Rp. 2,364,690, or around 76.93% must be used for physical maintenance activities